An assessment of the effect of the interaction of small dam development and management institutions on the quality of maintenance of small dams: a case of Mzingwane Catchment, Zimbabwe. - Mufute, Ngoni L.; Senzanje, A.; Kaseke, E. (Midlands State University, 2016)
Small dams are an important source of both primary and productive water for rural communities especially in resource and water scarce semi arid areas such as Mzingwane Catchment in Zimbabwe, which was the study area. However failure of small dams in this area can result in the deprivation of the communities of vital water sources. It was against this background that this study was carried out to assess the institutional collaboration and the effect of the existence and functional status of site specific small dam management structures on the quality of maintenance of small dams. Literature reviews, interviews and informal discussions were used to get an insight into how these institutions were interacting with each other as well as with the community. Observations and inspections were done to check the physical condition of small dams in order to assess quality of maintenance that was being carried out on them. A comparison was then made between the quality of maintenance being carried on a particular small dam and the existence and functional status of a dam committee at the respective small dams. The results of the study indicated that about 90% of the small dams studied were not being properly maintained. Of these, about 43% were not being maintained at all. Of the unmaintained and poorly maintained small dams, about 97% had either a non functional or none existent dam committee. Other major issues affecting the maintenance of small dams in the study area were the limited capacity of institutions, unclear roles of communities in the management of small dams, lack of resources and lack of incentives for locals willing to maintain the small dams. The study concluded that despite the existence of a government institution mandated to develop and maintain small dams, some form of effective and community based small dam management system has to be in place if dams are to be properly maintained especially in a resource scarce area. Recommendations were that the current small dams management structures need to be made more sustainable and effective. Some of the suggested ways of doing this include ensuring that within the leadership of these management structures, there is at least an influential member of community who is empowered to make decisions concerning the maintenance of the small dams. Levies and fees for productive uses of the small dams could be introduced to help contributing resources towards sustainable and effective functioning of dam committees and the maintenance of the small dams. Issues of unclear roles should also be resolved by making clear the policies on the role of communities and other stakeholders in the management of small communal dams.